Correction: Li et al. Automatic Point Cloud Registration for Large Outdoor Scenes Using a Priori Semantic Information. Remote Sens. 2021, 13, 3474 - Remote Sensing Editorial Office (Remote Sensing, 2022)
In the original article [...]